2007
DOI: 10.1248/cpb.55.346
|View full text |Cite
|
Sign up to set email alerts
|

Two New Glycosides from the Whole Plants of Glechoma hederacea L.

Abstract: Two new glycosides, 7S,7S,8R,8R-icariol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 13 publications
2
35
0
Order By: Relevance
“…From these functionalities, the aglycone suggested a 2,5-diaryltetrahydrofuranoid-type lignan. 29,30) In addition, HMBC correlations from the protons of one methoxyl group (d H 3.83, 3H, s) to C-3 (d C 148.4) showed that the methoxyl group was located at C-3, which was further confirmed by the ROESY correlation of the methoxyl group protons with H-2. HMBC correlations of protons of one methylenedioxy group with C-3Ј and C-4Ј determined the methylenedioxy group was located between C-3Ј and C-4Ј.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…From these functionalities, the aglycone suggested a 2,5-diaryltetrahydrofuranoid-type lignan. 29,30) In addition, HMBC correlations from the protons of one methoxyl group (d H 3.83, 3H, s) to C-3 (d C 148.4) showed that the methoxyl group was located at C-3, which was further confirmed by the ROESY correlation of the methoxyl group protons with H-2. HMBC correlations of protons of one methylenedioxy group with C-3Ј and C-4Ј determined the methylenedioxy group was located between C-3Ј and C-4Ј.…”
Section: Resultsmentioning
confidence: 75%
“…Compound 1 gave a quasi-molecular ion at m/z 599 [MϩNa] ϩ in its positive electrospray ionization (ESI)-MS spectrum and possessed a molecular formula of C 29 C-NMR data of 1 revealed that they are similar to those reported for micrandilactone D (4), 18,19) which was also isolated in this plant. Comparison of 1D NMR data, together with detailed HMBC and The relative stereochemistry of 1 was established by analysis of its ROESY NMR data and chemical shift comparison with those of micrandilactone D. 18,19) Biogenetically, H-C(5) was a-and Me(18) was b-oriented.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Several studies have reported that the chemical composition of G. hederacea includes alkaloids, sesquiterpenoids, triterpenoids, flavonoid glycosides, and rosmarinic acid, [20][21][22][37][38][39] but there is no report on the active constituent of G. hederacea as to anti-melanogensis. Further work is needed to define it.…”
Section: Discussionmentioning
confidence: 99%
“…20) It has been used as a folk medicine for centuries in the treatment of various ailments, e.g., asthma, bronchitis, colds, diabetes, and inflammation. 21) In addition, it has been reported that G. hederacea extract has anti-oxidant activity, 22) but no report on melanin biosynthesis or tyrosinase activity has been demonstrated. Hence we focused on the whitening effect y To whom correspondence should be addressed.…”
mentioning
confidence: 99%